Teenage-onset progressive myoclonic epilepsy due to a familial C9orf72 repeat expansion - van den Ameele, Jelle; Jedlickova, Ivana; Pristoupilova, Anna; Sieben, Anne; Van Mossevelde, Sara; Ceuterick-de Groote, Chantal; Hůlková, Helena; Matej, Radoslav; Meurs, Alfred; Van Broeckhoven, Christine; Berkovic, Samuel F; Santens, Patrick; et al. (Neurology, 2018)
BACKGROUND: The progressive myoclonic epilepsies (PME) are a heterogeneous group of disorders in which a specific diagnosis cannot be made in a subset of patients, despite exhaustive investigation. C9orf72 repeat expansions are emerging as an important causal factor in several adult-onset neurodegenerative disorders, in particular frontotemporal lobar degeneration and amyotrophic lateral sclerosis. An association with PME has not been reported previously. OBJECTIVE: To identify the causative mutation in a Belgian family where the proband had genetically unexplained PME. RESULTS: We report a 33-year old woman who had epilepsy since the age of 15 and then developed progressive cognitive deterioration and multifocal myoclonus at the age of 18. The family history suggested autosomal dominant inheritance of psychiatric disorders, epilepsy, and dementia. Thorough workup for PME including whole exome sequencing did not reveal an underlying cause, but a C9orf72 repeat expansion was found in our patient and affected relatives. Brain biopsy confirmed the presence of characteristic p62-positive neuronal cytoplasmic inclusions. CONCLUSION: C9orf72 mutation analysis should be considered in patients with PME and psychiatric disorders or dementia, even when the onset is in late childhood or adolescence.
Keywords: genetická predispozice k nemoci; lidé středního věku; Phenotype; fenotyp; Genetic Predisposition to Disease; DNA Repeat Expansion; dospělí; Brain; expanze repetic DNA; lidé; myoklonické epilepsie progresivní; ženské pohlaví; rodokmen; C9orf72 Protein; věk při počátku nemoci; Myoclonic Epilepsies, Progressive; Adult; Age of Onset; mozek; Pedigree; protein C9orf72; Middle Aged; Humans; Family; rodina; Female